2017
DOI: 10.1542/peds.2017-1117
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Social Media Intervention to Increase Vaccine Acceptance: A Randomized Controlled Trial

Abstract: Providing Web-based vaccine information with social media applications during pregnancy can positively influence parental vaccine behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 30 publications
5
157
0
1
Order By: Relevance
“…Passive interventions such as increasing knowledge or reminder-recalls have been shown to be the least effective in addressing vaccine hesitancy [40], and there is a need for more dialogue-based approaches targeted to specific sub-populations with an intended focus on social networks [40]. In a recent randomized-controlled trial, Glanz et al (2017) found that web-based information delivered on vaccines via social media platforms during pregnancy can have a positive impact on parental vaccine decisions [41]. However, communication strategies on immunization via social media are still not well understood and caution must be used to prevent legitimizing vaccine hesitancy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Passive interventions such as increasing knowledge or reminder-recalls have been shown to be the least effective in addressing vaccine hesitancy [40], and there is a need for more dialogue-based approaches targeted to specific sub-populations with an intended focus on social networks [40]. In a recent randomized-controlled trial, Glanz et al (2017) found that web-based information delivered on vaccines via social media platforms during pregnancy can have a positive impact on parental vaccine decisions [41]. However, communication strategies on immunization via social media are still not well understood and caution must be used to prevent legitimizing vaccine hesitancy [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is more effective to be respectful, stick to your message, identify where to find more information and exit the conversation, that is, limit direct engagement with those who have strong anti-vaccination views, either online or in person. Repeating their arguments as you attempt to refute them can be counterproductive as the misinformation may stick (21). SERIES CANVax -www.canvax.ca When you do engage in social media opportunities, do so wisely.…”
Section: Avoid Unproductive Debates and Be Respectfulmentioning
confidence: 99%
“…Tailored and targeted messages and information can help shape attitudes and improve uptake (22,23). As noted above, it can be useful to alert others to anti-vaccination tactics in public forums (20,21). Get your point across succinctly-remember that stories are often more powerful than dry facts and numbers-and steer readers to reputable sites for more quality information.…”
Section: Avoid Unproductive Debates and Be Respectfulmentioning
confidence: 99%
“…Similar to the themes of the broader noncompliance literature, additional studies of noncompliance with childhood immunizations draw on factors that have been found to influence parents’ vaccination hesitance and recommend what government should or could do to enhance compliance (e.g., Dubé et al ). Such recommendations emphasize the need to map and identify parents’ concerns (Oladejo et al ), the need to apply cognitive and social psychological insights while shaping interventions (Rossen et al ) as well as the need to develop web‐based interventions for the purpose of helping parents make evidence‐based decisions (Glanz et al ). Reviewing the literature on childhood vaccination noncompliance and public health interventions demonstrates the preponderance of top‐down approaches to public noncompliance, focusing on formal, long‐term interventions.…”
Section: Public Noncompliance With Childhood Immunizationmentioning
confidence: 99%